Peran Alex Evert Kawilarang dalam Menumpas DI/TII di Jawa Barat - miftahudin, abdul fatah; Kusdiana, Ading (Historia Madania: Jurnal Ilmu Sejarah, 2020)
Â Abstract The Darul Islam Movement / Indonesian Islamic Army (DI / TII) is a movement that emerged from dissatisfaction with the "Renville" agreement which impacted on TNI and army troops who had to migrate from West Java. on August 7, 1949 S. M. Kartosuwirjo as the leader declared the establishment of the Islamic State of Indonesia (NII) with its central position in West Java, especially in the East Priangan area. This made things even more difficult to control when on 19 December 1948 the Dutch reneged on the Renville Agreement and attacked the Indonesian capital in Yogyakarta, the Second War of Independence broke out, so this triggered the return of troops who migrated to their troops in West Java, but when it arrived at their troops were welcomed like enemies, finally a war broke out between three camps namely the TNI, Darul Islam and the Dutch troops. to the point where on December 27, 1949 the Dutch recognized the sovereignty of the Republic of Indonesia but DI / TII remained in principle wanting to establish a State based on Islamic sharia. The government finally held diplomacy but it did not find any bright spot so the government took the road to dissolve the DI / TII movement by force. Colonel AE Kawilarang, who at that time served as Commander of the Army and Territory III / West Java and was responsible for restoring security and peace in the region of West Java, thus the central government issued an Order to carry out "Operation Merdeka" in an effort to disperse DI / TII to re-lap Motherland. Â Keywords: DI/TII, Kawilarang, Supperssion DI/TII Abstrak Â Gerakan Darul Islam/Tentara Islam Indonesia (DI/TII) adalah gerakan yang muncul dari ketidakpuasan atas perjanjian â€œRenvilleâ€ yang berdampak pada pasukan TNI dan Â lasykar yang harus hijrah dari Jawa Barat. pada tanggal 7 Agustus 1949 S. M. Kartosuwirjo sebagai pemimpin menyatakan berdirinya Negara Islam Indonesia (NII) dengan pusat kedudukannya berada di Jawa Barat, terutama di daerah Priangan Timur. Hal ini membuat keadaan semakin sulit dikendalikan ketika pada tanggal 19 Desember 1948 Belanda mengkhinati Perjanjian Renville dan menyerang ibu kota RI di Yogyakarta maka pecahlah Perang Kemerdekaan II, sehingga ini menjadi pemicuÂ kembalinya tentaraÂ yang hijrah ke pasukan-pasukannya di Jawa Barat, tetapi ketika sampai di pasukan mereka disambut layaknya musuh, akhirnya pecahlah perang antara tiga kubu yaitu TNI, Darul Islam dan pasukan Belanda. sampai pada titik dimana pada tangggal 27 Desember 1949 Belanda mengakui kedaulatan RI tapi DI/TII tetap pada prinsipnya ingin mendirikan Negara yang berlandaskan syariâ€™at Islam. Pemerintah akhirnya mengadakan diplomasi akan tetapi tidak menemui titik terang sehingga pemerintah mengambil jalan untuk membubarkan gerakan DI/TII secara paksa. Kolonel A. E. Kawilarang yang pada saat itu menjabat sebagai Panglima Tentara dan Teritorium III/Jawa Barat serta bertanggung jawab terhadap pemulihan keamanan dan ketentraman wilayah Jawa Barat, dengan demikan pemerintah pusat mengeluarkan Perintah untuk menjalankan â€œOperasi Merdekaâ€ dalam usaha membubarkan DI/TII agar kembali kepangkuan Ibu Pertiwi. Â Kata kunci: DI/TII, Kawilarang, pembubaran DI/TII. Â